(untitled) (The Pakistan Development Review, 2019)
The book “The Pakistani Diaspora, Corridors of Opportunity and Uncertainty”, which is edited by Rashid Amjad, is a collection of 17 academic essays on Pakistani migrants and Pakistani diaspora in different countries. This book presents diverse viewpoints in the study of diaspora. This book does not just analyse the size of the diaspora in a chronological manner, but it also provides important understanding of the cost and benefits associated with migration and assimilation of the migrants’ families in new environments. In the first paper, the author tries to capture the salient features and dynamics of Pakistan’s “age of migration” across home and host countries. By 2017, the estimated diaspora was at 9.1 million – almost 5 per cent of Pakistan’s population. The labour class started to migrate to the UK in 1950s while highly skilled professionals started moving to the US and Canada in 1960s. The unskilled and semiskilled workers began to move to the Middle East in 1970s and due to easing off their visa policies in 1990s, migrants began moving to Europe, Singapore, Thailand, Malaysia and Australia from Pakistan. According to the author “A large number of people face losses in the struggle to migrate to foreign countries. A majority of illegal migrants are imprisoned in different countries while trying to reach Europe while dozens are killed on their way to Greece.”